Venous Thrombosis in Children with Brain Tumors - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
The incidence and significance of central venous access device (CVAD) dysfunction and symptomatic thrombosis were determined by retrospective review of 253 consecutive children diagnosed and treated for brain tumors at St Jude Children's Research Hospital, Memphis, TN, and Cleveland Clinic, OH.